2020
DOI: 10.3121/cmr.2020.1512
|View full text |Cite
|
Sign up to set email alerts
|

Suspected Neuro-invasive Powassan Virus Infection in a Pediatric Patient

Abstract: Powassan virus lineage II (POWV), also known as deer tick virus, is an emerging tick-borne pathogen transmitted by Ixodes scapularis, the natural vector for the organisms that causes Lyme disease, babesiosis, and anaplasmosis. POWV is the only tick-borne flavivirus in North America known to cause disease in humans. We present a suspected pediatric case of POWV infection in northern Wisconsin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Powassan virus (POWV) encephalitis was first reported in 1958, when the titer of POWV, a neuroinvasive arbovirus, was detected from the brain autopsy of a young boy who died in Powassan, Ontario [ 42 ]. It is a tickborne flavivirus-induced [ 43 , 44 ] disease that displays a wide spectrum of neuroinflammatory responses [ 45 ] in the brain and spinal cord including compromised blood–brain barrier integrity, enhanced infiltration of inflammatory T cells [ 46 , 47 ], severe microglial activation [ 47 ], and demyelination [ 48 ] of oligodendrocytes resulting neuronal toxicity. While it is not known if POWV can induce a similar acute immunosuppressive mechanism as seen in HHV6, a recent study [ 49 ] demonstrated that there is a robust proliferation of reactive Th1 cells in the spleens of the POWV-infected mice.…”
Section: Introductionmentioning
confidence: 99%
“…Powassan virus (POWV) encephalitis was first reported in 1958, when the titer of POWV, a neuroinvasive arbovirus, was detected from the brain autopsy of a young boy who died in Powassan, Ontario [ 42 ]. It is a tickborne flavivirus-induced [ 43 , 44 ] disease that displays a wide spectrum of neuroinflammatory responses [ 45 ] in the brain and spinal cord including compromised blood–brain barrier integrity, enhanced infiltration of inflammatory T cells [ 46 , 47 ], severe microglial activation [ 47 ], and demyelination [ 48 ] of oligodendrocytes resulting neuronal toxicity. While it is not known if POWV can induce a similar acute immunosuppressive mechanism as seen in HHV6, a recent study [ 49 ] demonstrated that there is a robust proliferation of reactive Th1 cells in the spleens of the POWV-infected mice.…”
Section: Introductionmentioning
confidence: 99%
“…Few cases have been reported in the US (189 cases total 2012-2021, CDC ArboNET), with most symptomatic individuals presenting with fever, headache, and weakness ( 166 ). Among children, cases remain limited predominantly to case reports ( 167 ). No cases of Powassan virus infection among pediatric SOT recipients have been reported, though an adult renal transplant recipient developed acute Powassan virus meningoencephalitis with transmission through receipt of blood products ( 168 ).…”
Section: Causative Viral Pathogensmentioning
confidence: 99%